STUDY OF VITAMIN-D AND HOMOCYSTEINE IN TYPE-2 DIABETES - G.S.R.KEDARI; G.S.R.HAREESH (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â DiabetesÂ mellitusÂ isÂ theÂ mostÂ commonÂ endocrineÂ disorderÂ inÂ developedÂ countriesÂ andÂ alsoÂ inÂ developingÂ countriesÂ likeÂ India. ItÂ hasÂ beenÂ hypothesizedÂ thatÂ vitaminÂ DÂ levelsÂ andÂ homocysteineÂ levelsÂ mayÂ contributeÂ inÂ theÂ pathogenesisÂ ofÂ diabetes. TheÂ aimÂ ofÂ ourÂ presentÂ studyÂ isÂ toÂ evaluateÂ theÂ roleÂ ofÂ vitamin DÂ andÂ homocysteineÂ inÂ type-2Â diabetes. Â WeÂ triedÂ toÂ assessÂ 25Â hydroxyÂ vitamin- DÂ LevelsÂ byÂ CLIAÂ methodÂ andÂ homocysteineÂ byÂ ELISAÂ method. ForÂ this, weÂ haveÂ takenÂ 50Â casesÂ ofÂ type-2Â diabeticÂ patientsÂ andÂ 75Â patientsÂ asÂ controls. AÂ significantÂ decreaseÂ Â inÂ theÂ levelsÂ ofÂ vitamin-DÂ andÂ significantÂ increaseÂ inÂ theÂ levelsÂ ofÂ homocysteineÂ wereÂ observed. ThisÂ suggestsÂ thatÂ vitamin-DÂ andÂ homocysteineÂ mayÂ playÂ a roleÂ inÂ developmentÂ ofÂ type-2Â diabetesÂ mellitus. KEYWORDS Vitamin- D, Homocysteine, DiabetesÂ mellitus.